2005
DOI: 10.1111/j.1439-0442.2005.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐nociceptive Efficacy of Carprofen, Levomethadone and Buprenorphine for Pain Relief in Cats following Major Orthopaedic Surgery

Abstract: A placebo-controlled, randomized blind study was conducted in cats (n = 60) after fracture repair to compare the analgesic effects as well as the side-effects of carprofen, buprenorphine and levomethadone during a 5-day treatment. Cats with severe shock symptoms or increases in blood urea nitrogen (BUN) and creatinine were excluded from the study. The cats were randomly assigned to four groups (n= 15). In group 1, carprofen was administered upon extubation at an initial dose of 4 mg/kg body weight, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 37 publications
6
42
0
3
Order By: Relevance
“…Buprenorphine has been shown to be superior to morphine, pethidine and oxymorphone in cats undergoing various types of surgery (Slingsby and Waterman-Pearson 1998, Dobbins and others 2002, Stanway and others 2002), but inferior to ketoprofen, meloxicam and carprofen in other studies (Slingsby and Waterman-Pearson 1998, Gassel and others 2005, Möllenhoff and others 2005). Although these results are conflicting, the dose of buprenorphine used was at the lower limit of the dosage range (0.006 to 0.01 mg/kg) for treatment of acute postoperative pain in cats.…”
Section: Discussionmentioning
confidence: 95%
“…Buprenorphine has been shown to be superior to morphine, pethidine and oxymorphone in cats undergoing various types of surgery (Slingsby and Waterman-Pearson 1998, Dobbins and others 2002, Stanway and others 2002), but inferior to ketoprofen, meloxicam and carprofen in other studies (Slingsby and Waterman-Pearson 1998, Gassel and others 2005, Möllenhoff and others 2005). Although these results are conflicting, the dose of buprenorphine used was at the lower limit of the dosage range (0.006 to 0.01 mg/kg) for treatment of acute postoperative pain in cats.…”
Section: Discussionmentioning
confidence: 95%
“…No changes in HR have been reported following methadone administration IM or SC (0.3 and 0.6 mg kg −1 , respectively) in cats (Mollenhoff et al, 2005;Bley et al, 2004). In the present study, HR values registered 20 min after injection decreased of about 28% in comparison to Tbase values, whilst during the intraoperative period no further decrease in heart rate was detected.…”
Section: Discussionmentioning
confidence: 43%
“…Previous studies reported an increase in cortisol levels compared to baseline preoperative values (MÖLLENHOFF et al, 2005) and in cats with higher pain scores and requiring rescue analgesia (EVANGELISTA et al, 2014). However, in another study differences in physiological parameters including cortisol and β-endorphins were not observed between cats that had undergone surgery and control cats (that had not) (CAMBRIDGE et al, 2000).…”
Section: Pain Recognitionmentioning
confidence: 69%